Security modeling for power system reliability evaluation. - Levi, V.A (IEEE Transactions on power systems)
This paper presents conceptual development, computation procedure and simulation results of the methodology for modeling security within reliability evaluation of power systems. The proposed approach takes into account activation of protection and automatic controls, local actions of operators, as well as centralized decisions taken by system operators. Transient stability, frequency variation during governor control, emergency and normal levels of line thermal protection, automatic generation control, overload rotation and economic dispatch are the main points of the developed procedure. It can be directly incorporated into the hybrid model for reliability evaluation of different operating states